Sest let zkuseností s endovenózním laserem v terapii varixů dolních kon etin - Kaspar, S; Pirkl, M; Príborská, J; Kaspar, D (Rozhledy v chirurgii, 2009)
AIMS: Endovascular techniques of saphenous ablation are the miniinvasive alternatives of the radical surgical treatment. This study summarizes our own clinical experience with endovenous laser. MATERIAL AND METHODS: During 6 year period we performed in total 723 endovenous laser procedures of trunk varicose veins of lower extremities in 630 patients. Every patient was preoperatively examined clinically and with color duplex machine. Primary varicose veins were operated on in 664 cases, in 59 cases the procedure was performed in recurrent varicose veins with reflux in the residual saphenous trunk. Post-operative follow-up (clinical and duplex ultrasound) was performed after 5 days and 1 month, 6 months and yearly thereafter. The results were evaluated by comparison of CEAP clinical class and quality of life (QoL) pre- and post-operatively, by the percentage of recanalizations and also using Kaplan-Meier life-table method. RESULTS: No thrombosis, nor pulmonary embolism were diagnosed in the post-operative period; from the whole cohort of 723 laser procedures, the postoperative data were available during different time periods in 718 cases (99.3%). Saphenous occlusion was verified in 97.3% after 1 month, non-occlusion or early reopening was seen in 2.7%. In total, 44 non-occluded trunk veins were found during the whole follow-up period (1-72 months, mean 15 months) which represents the final occlusion result of 93.9%. With stronger Kaplan-Meier analysis, we reached 88.9% occlusion rate during the follow-up period of 6 years. Cox regression analysis of factors influencing non-occlusion and early or late recanalisation of saphenous vein found 2 factors with statistical importance: energy per centimeter of vein length (p = 0.04) and laser power (p = 0.04). Cumulative rate of occlusions in 72 months horizon is significantly higher (94%) in patients treated with more than 50 J/cm compared to less than 50 J/cm (87%), log-rank test 0.039. When comparing the influence of laser power on the quality of saphenous occlusion, the treshold of 13W was set arbitrary based on median values in occluded and non-occluded cohorts and using the Kaplan-Meier survival method, the results of the treatment with power less than 13W and more than 13W were analysed. Using the power values less than 13W, the results were significantly better (p = 0.031) compared to power values of 13 W or more. Mean clinical CEAP classification improved from 2.22 (before operation) to 0.24 (1 month after) and 0.48 (last visit) and also QoL was significantly better in laser group compared to traditional surgery group (p < 0.001). The sick leave was also significantly shorter in the laser group ( median 0 days) compared to traditional group (median 40 days), p < 0.01. CONCLUSIONS: The results of endovenous laser ablation of varicose veins depend mainly on meticulous pre-operative ultrasound examination and sufficient technical parameters of the therapy. The present study supports the concept of "slow heating" during the endovenous laser treatment of varicose veins to achieve sufficient energy per centimetre of the vein and the optimal clinical outcome.
Keywords: dospělí; Female; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Male; Aged; Young Adult; varixy; lidé středního věku; senioři; mužské pohlaví; Varicose Veins; laserová terapie; Middle Aged; mladiství; Laser Therapy; Humans